Force Majeure Clause in the Covid-19 Vaccine Purchase Contract between Kimia Farma Tbk and Sinopharm - Herlan, Asep; Masturi, Frida Nurrahma; Iryatin, Al Fiani Nenden (Manunggal Halim Jaya, 2025)
Force majeure clauses in contracts are usually used as a complement to business agreements. The absence of special regulations that regulate in detail the force majeure clause often causes problems in the preparation of contracts. The force majeure clause became important and was widely used during the Covid-19 pandemic as a legal basis to overcome obstacles in the implementation of the parties' obligations due to unforeseen circumstances., through the Contract for the Purchase of Sars-Cov-2 Vaccine (Vero Cells), Inactivity or Covid-19 Vaccine (Vero Cells), Until now, the force majeure benchmark in the applicable legal provisions in Indonesia is regulated in a limited manner in Articles 1244-1245 of the Civil Code. The research method used was juridical normative by analyzing the force majeure clause in the Sars-CoV-2 Vaccine Purchase Contract (Vero Cell), Inactive or Covid-19 Vaccine (Vero Cell), Inactive between PT. Kimia Farma Tbk and Sinopharm China. The results of the study show that Article 10 Paragraph (4) of the Sars-CoV-2 Vaccine Purchase Contract (Vero Cell), Inactivation or Covid-19 Vaccine (Vero Cell), Deactivated between PT. Kimia Farma Tbk and Sinopharm China did not comply with one of the provisions in Articles 1244-1245 of the Civil Code, namely: elements that were not anticipated beforehand. Based on the results of the analysis, this study is expected to provide legal recommendations for the preparation of force majeure clauses in international business contracts in the future to be more in line with the principles of Indonesian civil law.